Stagnation-point flow and heat transfer over an exponentially stretching/shrinking inclined plate in a micropolar fluid - Abu Bakar, Fairul Naim; Soid, Siti Khuzaimah; Norzawary, Nur Hazirah Adilla; Sohut, Farizza Haniem (Penerbit Akademia Baru, 2024)
The study investigates the fluid flow characteristics and heat transfer over an exponentially stretching/shrinking inclined plate immersed in a micropolar fluid. The micropolar fluid model considers the rotational effects of microelements relevant to complex industrial fluid behavior. Using similarity variables, the governing equations for fluid flow and heat transfer are transformed from Partial Differential Equations (PDEs) to Ordinary Differential Equations (ODEs), and appropriate boundary conditions are incorporated to simulate the behavior of the micropolar fluid over the inclined plate. The ODEs are numerically solved using MATLAB software with BVP4c, and the results are compared with previous findings, showing good agreement. The effects of critical parameters such as plate inclination angle, stretching/shrinking rate, and micropolar fluid parameters are examined. Notably, the micropolar parameter significantly influences the skin friction for stretching and shrinking flows. An increase in the micropolar parameter leads to increased skin friction for stretching flows, while for shrinking flows, the skin friction decreases within a specific range of stretching/shrinking values. The behavior of the local couple stress becomes complex as the micropolar parameter increases. Additionally, the local Nusselt number decreases as the micropolar parameter increases for shrinking flows, indicating a reduction in heat transfer from the solid surface during shrinking flow. Moreover, an increase in the Sherwood number suggests a relatively slower mass transfer rate than momentum transfer. These findings offer valuable insights into the behavior of micropolar fluids over exponentially stretching/shrinking inclined plates, guiding optimizing heat transfer and fluid flow in practical engineering systems.